2002
DOI: 10.1046/j.1445-2197.2002.02484.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting surgical outcome in the elderly at Auckland Hospital

Abstract: The ASA, timing and duration of surgery were the most significant factors affecting patient outcome. Age had a less important effect. Arranged surgery and short operative duration have a favourable outcome in selected elderly patients. Therefore, the elderly should not be denied indicated major abdominal surgery on basis of age alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 9 publications
1
21
1
6
Order By: Relevance
“…The median (range) ISS was 4 (1-16) and the median (range) GCS was 15 (12)(13)(14)(15). Four (4.3%) patients were admitted to the Intensive Care Unit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median (range) ISS was 4 (1-16) and the median (range) GCS was 15 (12)(13)(14)(15). Four (4.3%) patients were admitted to the Intensive Care Unit.…”
Section: Resultsmentioning
confidence: 99%
“…Even low energy trauma in the elderly can be serious because they have decreased physiological reserve and associated comorbidities 8,14 . It is important to note that age alone does not reflect the patient's physiological status and each patient should be considered individually 9,15 . Hazards at home, such as uneven surface or slippery floor, can increase the risk of falls in the elderly 11,16 .…”
mentioning
confidence: 99%
“…The American Society of Anesthesiologist Physical Status Classification (American Score Anesthesiologist-ASA) is routinely used to evaluate the risk of death in each patient who is candidate to surgery (Dripps et al, 1961;Owens et al, 1978). Several studies demonstrated that the ASA score is highly reliable also in older patients in different surgical settings (Hosking et al, 1989;Bufalari et al, 1996;El-Haddawi et al, 2002;Arenal and Bengoechea-Beeby, 2003). The Acute Physiology and Chronic Health Evaluation (APACHE) is another valid tool for the risk assessment in patients of a wide range of age, particularly in those who are candidate to emergent surgical procedures (Knaus et al, 1985;Giangiuliani et al, 1989;Barie et al, 1995;Koperna et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true for patients, such as ours, that can be described using the term "frailty, " a multifactorial state of general physical weakness, often under recognized patient vulnerability and decreased physiologic reserve. Perioperative risk is heterogeneous in this group, as age and comorbidities may fail to accurately predict functional deficits and often cannot adequately predict operative and perioperative morbidity and mortality in this population group [35,[40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%